Cash transfers and intimate partner violence (IPV) in low- and middle-income settings: A joint research agenda to inform and practice - Peterman, Amber; Roy, Shalini; Hidrobo, Melissa; Billings, Lucy; Palermo, Tia; Barrington, Clare; Ranganathan, Meghna; Buller, Ana Maria; Heise, Lori; Phillips, Pace; Bates-Jeffreys, Ellen (International Food Policy Research Institute, 2021)
Over the last five years, there has been increasing interest from global stakeholders in the relationship between cash transfers and gender-based violence, and in particular, intimate partner violence (IPV). Interest has grown both within the development and humanitarian spaces, although empirical research is mainly concentrated in the former. A mixed-method review paper published in 2018 found that, across 22 quantitative or qualitative studies in low- and middle-income countries (LMICs), the majority (73%) showed that cash decreased IPV; however, two studies showed mixed effects, and several others showed heterogenous impacts (Buller et al. 2018). A more recent meta-analysis of 14 experimental and quasiexperimental cash transfer studies found average decreases in physical/sexual IPV (4 percentage points (pp)), emotional IPV (2 pp) and controlling behaviors (4 pp) (Baranov et al. 2021). A feature of this literature is the high representation of evaluations from Latin America, primarily government conditional cash transfer programs. In addition, programming was generally focused on poverty-related objectives, and none of the programming was explicitly designed to affect IPV or violence outcomes more broadly.